2007
DOI: 10.1186/1472-6963-7-172
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of guidelines for antihypertensive care in Finland

Abstract: Background: Hypertension is one of the major causes of disease burden affecting the Finnish population. Over the last decade, evidence-based care has emerged to complement other approaches to antihypertensive care, often without health economic assessment of its costs and effects. This study looks at the extent to which changes proposed by the 2002 Finnish evidencebased Current Care Guidelines concerning the prevention, diagnosis, and treatment of hypertension (the ACCG scenario) can be considered cost-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…Three articles presented economic evaluations of a national policy or action plan [ 63 65 ]. The new Finnish hypertension care guidelines were compared with previous ones [ 64 ], which did not incorporate lifestyle intervention; the new guidelines were estimated to save an additional 49,000 life years. The Dutch national action plan for counteracting obesity included a community-based intervention in which 90% of the population was screened and received lifestyle advice; an intensive lifestyle program was applied to 10% of the overweight adults in a healthcare setting.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles presented economic evaluations of a national policy or action plan [ 63 65 ]. The new Finnish hypertension care guidelines were compared with previous ones [ 64 ], which did not incorporate lifestyle intervention; the new guidelines were estimated to save an additional 49,000 life years. The Dutch national action plan for counteracting obesity included a community-based intervention in which 90% of the population was screened and received lifestyle advice; an intensive lifestyle program was applied to 10% of the overweight adults in a healthcare setting.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have conducted analyses to demonstrate cost savings and cost-effectiveness of strategies intended to ameliorate hypertension. For example, strategies shown to be cost-effective include a nurse-administered, tailored behavioral intervention in the United States, 10-12 a national hypertension prevention and control program in Israel, 13 a national hypertension treatment program in Germany, 14 an elderly health examination program including hypertension screening in Taiwan, 15 an adherence-improving program (the Medication Events Monitoring System) in hypertensive patients in the Netherlands, 16 guidelines for antihypertensive care in Finland, 17 and ambulatory blood pressure monitoring in Spain. 18 In China, however, no studies have documented cost savings or cost-effectiveness of programs intended to prevent and control hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In the same context, Montgomery et al [28], in their analysis, demonstrated improved treatment efficiency for men and advanced age, at even lower ICERs than the ones reported here, a fact probably explained by the higher risk population included in their study. Beyond the aforementioned, data in favor of hypertension treatment, from an economic evaluation point of view, have been published for healthcare settings of Canada [29], Finland [30], the UK [31] and elsewhere. However, it should be kept in mind, when attempting to undertake international comparisons, that direct comparability of cost-effectiveness results across different Ten-year ICERs depending on starting age of treatment.…”
Section: Discussionmentioning
confidence: 98%